Association of Hypertension and Ischaemic ECG Changes in Type II Diabetes Mellitus - Rai, Chandra Kala; Poudel, Nimesh (Journal of Chitwan Medical College, 2019)
Background: Type 2 diabetes mellitus (T2DM) is one of the most common metabolic disorders to the current generation. It usually leads to multi-systemic complications such as cardiovascular diseases, proteinuria, micro albuminuria, retinopathy, hypertension, ischaemic changes and chronic kidney disease. These complications increase the morbidity and mortality of patients. The prolonged hyperglycemia leads to vascular damage. It causes insufficient blood flow to the cardiac muscles which may cause myocardial or cardiac ischaemia. The aim of this study was to find out the prevalence of hypertension and ischaemic ECG changes in T2DM patients attending Kathmandu Medical College. Methods: Total 360 type 2 diabetic patients were included. Blood pressure was measured and electrocardiogram (ECG) was recorded by 12 leads ECG. Statistical analysis was done using SPSS version 16. p<0.05 was considered to be statistically significant. Results: The mean age of the patients was 66.88 ± 1.52 years, age ranging from 40 – 95 years. In this study 168 patients (46.66%) had systolic hypertension, 204 patients (56.67%) had diastolic hypertension and 126 (35%) had both systolic and diastolic hypertension. About 103 (28.61%) showed ECG changes in hypertensive patients. Only 4 (1.11%) non- hypertensive had ECG changes. This study showed statistically significant relation of hypertension and ischaemic ECG changes in type 2 diabetes mellitus cases with p- value 0.03. Conclusions: There is a high prevalence of hypertension among T2DM patients. In these patients, there is a statistically significant association between hypertension and ischaemic ECG changes.